Design and Realize a Snake-Like Robot in Complex Environment. (3rd February 2019) - Liu, Bingqi; Liu, Mingzhe; Liu, Xianghe; Tuo, Xianguo; Wang, Xing; Zhao, Shibo; Xiao, Tingting
Abstract : Aiming at high performance requirements of snake-like robots under complex environment, we present a control system of our proposed design which utilizes a STM32 as the core processor and incorporates real-time image acquisition, multisensor fusion, and wireless communication technology. We use Solidworks to optimize the design of head, body, and tail joint structure of the snake-like robot. The system is a real-time system with a simple-circuit structure and multidegrees of freedom are attributed to the flawless design of control system and mechanical structure. We propose a control method based on our simplified CPG model. Meanwhile, we improve Serpenoid control function and then investigate how different parameters affect the motion gait in terms of ADAMS emulation. Finally, experimental results show that the snake-like robot can tackle challenging problems including multi-information acquisition and processing, multigait stability, and autonomous motion and further verify the reliability and accuracy of the system in our combinatory experiments.